Let's bind a friendly co-existence with nature - Abdul Razak, Mohd. Abbas (Muslim Welfare Organisation of Malaysia, 2016)
The topic on man and nature is an inseparable one that has been discussed over the centuries. This topic has caught the attention of many scholars of diverse specialization. Major religions of the world preach that the universe/nature has been created long before the arrival of man on this planet. Ever since man came to exist on this planet, it has gone through a dramatic change, particularly with the coming age of modernization, industrialization, colonization and now globalization. Geologists and environmentalists say that the face of the earth is constantly changing at a rapid scale due to pollution of all kinds. Pollution on land, in sea, forest, mountains, in space, global warming, melting of the ice at the poles, war, and many more pose a threat to human, wild and marine lives. The main culprit in causing the pollution and environmental degradation is none other than man himself. Man in his greed for riches and dominance has caused great destruction to the living conditions in this planet.